Applicability of iron (III) trimesic (Fe-BTC) to enhance lignin separation from pulp and paper wastewater - Bhuckchanya Pangkumhang,; Panitan Jutaporn,; Kwannapat Sorachoti,; Pummarin Khamdahsag,; Visanu Tanboonchuy, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study assesses the application of iron (III) trimesic (Fe-BTC) as a coagulant-flocculant to remove lignin from pulp and paper (P&P) wastewater. In this research, Fe-BTC was characterized by X-ray diffraction (XRD), while the functional groups of Fe-BTC and lignin were analyzed by Fourier transform infrared (FT-IR) spectroscopy. Scanning electron microscopy (SEM) determined the surface morphology of the material. The influential parameters affecting lignin removal included the initial lignin concentration, the quantity of Fe-BTC, and the pH which were investigated using a single batch mixing system. The experimental and optimum operational conditions were determined using Box-Behnken design (BBD). Fe-BTC dosage plays a major role in efficiently removing lignin, while the pH and initial lignin concentration had no significant effect. Greater than 80% removal efficiency could be achieved with a Fe-BTC dosage as low as 2 g/L. The proposed mechanism of lignin aggregation was that Fe molecules were released from unsaturated sites of Fe-BTC and then formed new bonds with O in the methoxy lignin group. The interaction between Fe-BTC and lignin was π-π stacking (benzene ring), which explains the formation of F-O bonds in the lignin sludge.